GENERALISASI METODE GAUSS-SEIDEL UNTUK MENYELESAIKAN SISTEM PERSAMAAN LINEAR - Andri Ramadhan; Syamsudhuha '; Asli Sirait (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article presents a generalized Gauss-Seidel method for solving system of linear equations. This article is a review of Salkuyeh's paper [Numerical Mathematics, A Journal of Chinese Universities, 16: 164-170, 2007]. Some examples are presented at the end of discussion.